An Improved Hybridization Of Tournament And Genetic Algorithm For Solving Various Engineering Design Optimization Problems - Bala, S; Pal, P (Michael Faraday IET International Summit 2015, 2015)
An improved hybrid algorithm of Tournament and Genetic Algorithm are presented for solving engineering design optimization problems. In our work, we have proposed an efficient hybrid algorithm based on tournament game concept and Genetic Algorithm, called the Tournament Genetic Algorithm (TGA), has been introduced for solving the classical optimization and Engineering design optimization problems. Five classical constrained optimization problems and two well known construction optimization problems have been solved and the corresponding outcomes were verified with other known optimization methods. Finally, to study the performance of our proposed technique with other well known optimization techniques, a comparative analysis has been made which are previously reported in the existing literature.